2018
DOI: 10.15252/emmm.201708558
|View full text |Cite
|
Sign up to set email alerts
|

A novel CHCHD10 mutation implicates a Mia40‐dependent mitochondrial import deficit in ALS

Abstract: CHCHD10 mutations are linked to amyotrophic lateral sclerosis, but their mode of action is unclear. In a 29‐year‐old patient with rapid disease progression, we discovered a novel mutation (Q108P) in a conserved residue within the coiled‐coil‐helix‐coiled‐coil‐helix (CHCH) domain. The aggressive clinical phenotype prompted us to probe its pathogenicity. Unlike the wild‐type protein, mitochondrial import of CHCHD10 Q108P was blocked nearly completely resulting in diffuse cytoplasmic localization and reduced stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 38 publications
(66 reference statements)
3
43
0
Order By: Relevance
“…Only a mutant lacking a C-terminal CHCHD domain failed to rescue the C2C10H S81L -induced phenotype ( fig. S3D), which may reflect the failure of CHCHD10 ΔCHCHD mitochondrial localization, as previously reported (34).…”
Section: Chchd10 S59l -Induced Phenotypes Are Rescued By Wt and Mutansupporting
confidence: 81%
See 2 more Smart Citations
“…Only a mutant lacking a C-terminal CHCHD domain failed to rescue the C2C10H S81L -induced phenotype ( fig. S3D), which may reflect the failure of CHCHD10 ΔCHCHD mitochondrial localization, as previously reported (34).…”
Section: Chchd10 S59l -Induced Phenotypes Are Rescued By Wt and Mutansupporting
confidence: 81%
“…Our findings with CHCHD10 G58R and CHCHD10 G66V are more difficult to interpret because of their disparate results in Drosophila and HeLa cells. Although similar steady-state expression levels occurred in Drosophila and HeLa cells, CHCHD10 G58R and CHCHD10 G66V expression is considerably reduced when compared with that of CHCHD10 WT or CHCHD10 S59L (34).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Analogously, other studies reported that the overexpression of mutant versions of mitochondrial proteins, such as NUBPL and FOXRED1, was able to reverse the pathological phenotype in patient cells (Tucker et al , ; Formosa et al , ). The stimulation of mitochondrial import of the pathogenic mutant CHCHD10 was recently proposed as a possible therapeutic strategy for amyotrophic lateral sclerosis (Lehmer et al , ). Our data suggest that the inhibition of excessive degradation by the proteasome can rescue mitochondrial function in diseases that are associated with the mislocalization and premature degradation of mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, other studies reported that the overexpression of mutant versions of mitochondrial proteins, such as NUBPL and FOXRED1, was able to reverse the pathological phenotype in patient cells (Formosa et al, 2015;Tucker et al, 2012). The stimulation of mitochondrial import of the pathogenic mutant CHCHD10 was recently proposed as a possible therapeutic strategy for amyotrophic lateral sclerosis (Lehmer et al, 2018). Our data suggest that the inhibition of excessive degradation by the proteasome can rescue mitochondrial function in diseases that are associated with the mislocalization and premature degradation of mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 89%